Large Hepatic Subcapsular Hematoma Secondary to Double-J Stent Placement - Blas, Leandro (J Endourol Case Rep, 2019)
Introduction and Background: Urinary diversion with the endoscopic Double-J stent is a frequent procedure; complications can include irritation, suprapubic or flank pain, vesicoureteral reflux, hematuria, or urinary infection. We report a case of hepatic subcapsular hematoma secondary to Double-J stent placement. Case Presentation: A 28-year-old woman presented with a history of Sjögren's disease, nephrocalcinosis, and chronic kidney disease (CKD). The patient underwent multiple percutaneous and endoscopic procedures during the previous 2 years: right kidney: extracorporeal shock wave lithotripsy (SWL) × 4, ureteroscopic lithotripsy × 2, percutaneous nephrolithotomy (PCNL), and retrograde intrarenal surgery; left kidney: SWL × 2, ureteroscopic lithotripsy × 5, and PCNL. Ultrasound imaging showed severe dilation in the right kidney and moderate dilation in the left kidney. CT scanning without contrast revealed a right pyelourethral dilation caused by a 13 mm ureteral lithiasis; also, cortical atrophy was observed. Urosepsis with exacerbated CKD was diagnosed and bilateral 7F Double-J stents were placed on both sides under general anesthesia. On postoperative day (POD) 8, the patient presented with pain in the right hemithorax and dullness to percussion. CT scans showed a heterogeneous hepatic subcapsular collection, of 15 × 7 × 23 cm, of hematic aspect, displacing vascular structures, and no active bleeding. Treatment was expectant and symptomatic. On POD 16, a new CT scan ruled out progression of the hematoma. The patient was finally discharged on POD 19. Four months later, bilateral semirigid ureteroscopy showed a right ureteral lithiasis of 8 × 7 mm, which was fragmented with a holmium laser. Nineteen months after the first episode, the patient is asymptomatic, with no residual lithiasis or hepatic hematoma. Conclusion: This case shows a very rare complication of Double-J stent placement that could be managed by conservative treatment.